Thermal properties of thermochemical heat storage materials - Bird, Julianne; Humphries, Terry; Paskevicius, Mark; Poupin, Lucas; Buckley, Craig (ROYAL SOC CHEMISTRY, 2020)
This journal is © the Owner Societies. The thermal conductivity, thermal diffusivity and heat capacity of materials are all vital properties in the determination of the efficiency of a thermal system. However, the thermal transport properties of heat storage materials are not consistent across previous studies, and are strongly dependent on the sample composition and measurement method. A comprehensive analysis of thermal transport properties using a consistent preparation and measurement method is lacking. This study aims to provide the foundation for a detailed insight into thermochemical heat storage material properties with consistent measurement methods. The thermal transport properties of pelletised metal hydrides, carbonates and oxides were measured using the transient plane source method to provide the thermal conductivity, thermal diffusivity and heat capacity. This information is valuable in the development of energy storage and chemical processing systems that are highly dependent on the thermal conductivity of materials.